Rivaroxaban real-world evidence: Validating safety and effectiveness in clinical practice - Beyer-Westendorf, Jan; Camm, A. John; Coleman, Craig I.; Tamayo, CAPT Sally (Thrombosis and Haemostasis, 2016)
Randomised controlled trials (RCTs) are considered the gold standard of clinical research as they use rigorous methodologies, detailed protocols, pre-specified statistical analyses and well-defined patient cohorts. However, RCTs do not take into account the complexity of real-world clinical decision-making. To tackle this, real-world data are being increasingly used to evaluate the long-term safety and effectiveness of a given therapy in routine clinical practice and in patients who may not be represented in RCTs, addressing key clinical questions that may remain. Real-world evidence plays a substantial role in supporting the use of non-vitamin K antagonist (VKA) oral anticoagulants (NOACs) in clinical practice. By providing data on patient profiles and the use of anticoagulation therapies in routine clinical practice, real-world evidence expands the current awareness of NOACs, helping to ensure that clinicians are well-informed on their use to implement patient-tailored clinical decisions. There are various issues with current anticoagulation strategies, including under- or overtreatment and frequent monitoring with VKAs. Real-world studies have demonstrated that NOAC use is increasing (Dresden NOAC registry and Global Anticoagulant Registry in the FIELD-AF [GARFIELD-AF]), as well as reaffirming the safety and effectiveness of rivaroxaban previously observed in RCTs (XArelto on preveNtion of sTroke and non-central nervoUS system systemic embolism in patients with non-valvular atrial fibrillation [XANTUS] and IMS Disease Analyzer). This article will describe the latest updates in real-world evidence across a variety of methodologies, such as non-interventional studies (NIS), registries and database analyses studies. It is anticipated that these studies will provide valuable clinical insights into the management of thromboembolism, and enhance the current knowledge on anticoagulant use and outcomes for patients.